(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
in the 10-year period when Shaykhzoda began to live in Tashkent, she not only mastered the Uzbek language, but also lovingly studied Navoi’s creativity, including writing poems and articles in the same language, translating Pushkin’s works, researching Chulpan creativity